Nursing Involvement and Safety Participation among Secondary Health Care Nurses in Jordan: The Mediating Effect of Work Environment - Ashour, Abdallah; Hassan, Zuraida (International Review of Management and Marketing, 2019)
This study suggests that the work environment would mediate the relationship between nursing involvement on nurse’s safety participation. Survey data obtained among 517 nurses from the Jordanian ministry of health, Jordan. Smartpls 3.2.8 was applied to test the hypotheses that comprised both the direct effect of nursing involvement on safety participation and mediating role of work environment on these relationships and consequently bootstrapping was conducted to investigate the standard error of the estimate and t-values. Results from partial least squares analysis show that nursing involvement positively relates to safety participation. Additionally, work environment mediates the relationships between, nursing involvement and safety participation. This contributes to the utility of social exchange theory (SET). Furthermore, to achieve an optimally safe hospital environment, hospital management should encourage employees by involving them in safety activities and decision-making processes within the hospitals and consider enhancing the work environment to improve hospital safety. Keywords: Nursing Involvement, Work Environment, Safety Participation, Safety Performance JEL Classification: M12 DOI: https://doi.org/10.32479/irmm.8120